Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1017/s2045796020000785
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a housing support team intervention with a recovery-oriented approach on hospital and emergency department use by homeless people with severe mental illness: a randomised controlled trial

Abstract: Aims Many people who are homeless with severe mental illnesses are high users of healthcare services and social services, without reducing widen health inequalities in this vulnerable population. This study aimed to determine whether independent housing with mental health support teams with a recovery-oriented approach (Housing First (HF) program) for people who are homeless with severe mental disorders improves hospital and emergency department use. Methods We did a randomised controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 49 publications
(63 reference statements)
0
30
0
Order By: Relevance
“…For participants with high needs at baseline, receiving HF with ACT support, there were no significant effects on all-cause and mental health hospitalizations, but a significant reduction in the number of days in hospital as well as the number of ED visits. A study of an HF intervention in four French cities among high-need participants similarly found no significant effects on hospitalization or ED visits, but reduced inpatient days [ 26 ]. Another randomized study of the effects of permanent supportive housing for chronically homeless high users of multiple systems in Santa Clara County, California (USA) found no effects on ED or inpatient care use [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…For participants with high needs at baseline, receiving HF with ACT support, there were no significant effects on all-cause and mental health hospitalizations, but a significant reduction in the number of days in hospital as well as the number of ED visits. A study of an HF intervention in four French cities among high-need participants similarly found no significant effects on hospitalization or ED visits, but reduced inpatient days [ 26 ]. Another randomized study of the effects of permanent supportive housing for chronically homeless high users of multiple systems in Santa Clara County, California (USA) found no effects on ED or inpatient care use [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an ideal world, the 'step-by-step' model aims to facilitate the progressive movement of homeless people from the streets to emergency shelters (ETHOS 2), and then onwards to stabilization shelters (ETHOS 3) in order to help prepare them for private housing. This model remains dominant at the policy level, despite the existence of other models like Housing First, which promote direct and unconditional access to housing and have proven more effective at producing housing stability [29,30]. Our study shows (Figure 4) that there were very few instances of people moving from homeless directly to private housing, and lots of people in the step-by-step model, experiencing long stays in emergency shelters and little access to stabilization shelters at a later stage.…”
Section: Discussionmentioning
confidence: 99%
“…The overrepresentation of socially favored patients with BD may also suggest lower access to hospital care in deprived patients with BD than in controls. Previous studies have suggested that, among deprived individuals, patients with severe mental illnesses, such as BD, are some of the most underserved and undertreated populations (Nielsen et al, 2019 ; Tinland et al, 2020 ). In a recent study on homeless individuals, the main negative predictors for hospital use were a lower social functioning score and BDs (Loubière et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%